Perceived social support and the sense of coherence in patient–caregiver dyad versus acceptance of illness in cancer patients - Pasek, Małgorzata; Dębska, Grażyna; Wojtyna, Ewa (Journal of clinical nursing, 2017)
Background Acceptance of illness is a significant determinant of further coping with a disease. Development of illness acceptance may be associated with the sense of coherence and perception of social support. Cancer is an example of a crisis situation, which affects both the patient and his/her close relatives. Consequently, acceptance of illness may be influenced by factors originating from both sides of caregiver–patient dyad. The aim of this study was to analyse direct and indirect interrelationships between perceived support and the sense of coherence in patient–caregiver dyad, and acceptance of illness in cancer patients. Design Cross‐sectional study. Methods The study included 80 dyads composed of cancer patients and their caregivers. Only cancer patients undergoing oncological treatment at the time of the study, for at least 3 months but no longer than 12 months, were enrolled. All subjects completed perceived support subscale included in the Berlin Social Support Scales, sense of coherence‐29 questionnaire to determine the sense of coherence and Acceptance of Illness Scale. Results Compared to cancer patients, their caregivers presented with significantly lower levels of perceived social support and weaker sense of coherence. The sense of coherence in caregivers and patients was determined by their perceived support levels. The sense of coherence in caregivers turned out to be a key resource influencing acceptance of illness in cancer patients, both directly and indirectly, via their perceived social support and their sense of coherence. Conclusions The sense of coherence, an intrinsic psychological factor determined by social support, is an important determinant of illness acceptance. Functioning of cancer patients is also modulated by psychosocial characteristics of their caregivers. Relevance to clinical practice Greater support offered to caregivers may substantially strengthen the sense of coherence in caregivers and cancer patients and, therefore, may improve the functioning of patient–caregiver dyad in a situation of neoplastic disease.